Polsko-niemiecki traktat o dobrym sąsiedztwie i przyjaznej współpracy na forum Bundestagu - Trzcielińska-Polus, Aleksandra (Rocznik Polsko-Niemiecki, 2016)
The Polish-German Treaty of Good Neighborliness and Friendly Cooperation that was signed between the Federal Republic of Germany and the Republic of Poland a quarter-century ago has repeatedly been the subject of debates, interpellations and deputies’ questions at the German Federal Parliament. This article presents the most important debates and documents of the Bundestag, in which both deputies and members of the government expressed their opinions and positions with regard to the provisions of the treaty and its implementation. The aim of this study is to show changes to and differences in the rhetoric of parliamentarians representing various factions and representatives of the government in relation to this treaty over 20 years (i.e., from its signature and ratification in 1991 to the celebrations of its twentieth anniversary in 2011), and to present the priority issues raised in its context.